PENGARUH TEMPERATUR SINTERING TERHADAP SIFAT OPTIK LAPISAN TIPIS ZINC OXIDE (ZnO) YANG DIDEPOSISI DIATAS SUBSTRAT KACA DAN APLIKASINYA UNTUK MENDEGRADASI PEWARNA METHYLENE BLUE - Nur Hasim Efendi; Heri Sutanto (Youngster Physics Journal, 2014)
In this research, ZnO  thin films have been successfully deposited on glass substrates by spraycoatingtechniquewith avariety the sintering temperature of 300 °C , 400 °C , 450 °C and 550 °C. Optical properties ZnO thin films were characterized by using UV-Vis spectroscopy. The ability ofphotocatalyst of ZnOfordegradation ofmethylene bluecolorwas observedthrough the absorbance test by using UV-Vis to obtain the percentage of color degradation. The results showed that the sintering temperature of ZnO affects the value of energy Gap of ZnO thin film. Higher sintering temperature resulted in higher energy gap. The largest gap energy generated from the ZnO sintering temperature of 450 ˚ Cwith values Eg 3.03 eV. ZnO photocatalyst activity of test results have been able to degrade methylene blue up to 97.62% were obtained from ZnO thin layer of sintering temperature of 450 ˚ C.Keywords: Photocatalyst, Spray coating, ZnO, Band gap energy, Methylene blue, Sintering temperature.